Young University Students’ Academic Self-Regulation Profiles and Their Associated Procrastination: Autonomous Functioning Requires Self-Regulated Operations - Valenzuela, Rafael; Codina, Nuria; Castillo, Isabel; Pestana, José Vicente (Frontiers in Psychology, 2020)
Students’ autonomous self-regulation in learning requires not only self-motivation, but also volition. In this regard, self-regulation entails strategies both for enhancing self-motivation (goal setting, learning from mistakes) and volitional regulation (strategic decision making). Furthermore, personal characteristics, such as trait-level perseverance or grit may significantly influence both motivation and volition. Subpar self-regulation leads to procrastination, which has been defined as a volitional self-regulation problem – a tendency towards dysregulated behaviour that affects young people’s autonomy and well-being. Previous research has confirmed a negative relationship between self-regulation and procrastination. However, more precision is demanded a) in examining the intertwined roles of motivational and volitional aspects of self-regulation for procrastination, and b) in distinguishing between different medium, and between medium and high levels of self-regulation. Consequently, it has been suggested that this could be accomplished by means of person-centred analyses, aimed at identifying distinct naturally occurring students’ self-regulation profiles. Participants were 994 young university students from one public and one private university in Catalonia (41.0% men, 58.4% women, and 0.5% non-binary gender), aged from 18 to 24 years (M = 19.69, SD = 1.41). Sampling method was intentional, with proportional quotas by sex, academic year, and area of knowledge. The instrument used for data collection incorporated the Short Spanish Self-Regulation Questionnaire (SSSRQ), which includes four dimensions: perseverance, learning from mistakes, goal setting, and decision making; and the Pure Procrastination Scale (PPS), which considers three dimensions: decisional procrastination, implemental delay and lateness. Results obtained by means of cluster analysis distinguished between high and low academic self-regulation profiles, and also between these and two different medium self-regulation profiles, each with specific emphases on particular volitional shortcomings. These profiles and their relations with procrastination dimensions allow a joint evaluation of cognitive motivational strategies (goal setting, decision making, learning from mistakes, and decisional procrastination) together with behavioural aspects (perseverance, implemental delay), considered in the constructs of academic self-regulation and pure procrastination. From this joint evaluation, guidelines are suggested for promoting autonomy among young university students, to the detriment of procrastination, thereby – and in accordance with previous research – enhancing students’ well-being and growth.